Fake news and real news: What are their characteristics and how to identify them in a school and in COVID-19 pandemic context? A proposal for scientific literacy adapted to emergency remote education (Research, Society and Development, 2021)
This case study aimed to apply, adapt and then evaluate a didactic approach to combat fake news, through scientific literacy in the context of emergency remote education (ERE) with a focus on COVID-19. For this, virtual workshops were held in 2020 with high school students from two public schools in the state of Maranhão, Brazil. All the ethical guidelines of Resolution CNS 510/2016 were followed. In the workshops, the students were exposed to the situation-problem of differentiating fake news from reliable news by identifying typical characteristics of either type of information. There were 18 characteristics for fake news and 18 characteristics for reliable news, of which 50% and 83.3% are unpublished, respectively. In addition, four fake news features and four reliable news features were observed by the students exclusively related to COVID-19. Thus, the adaptation to ERE that is proposed in the present study proved effective and could subsidize any work that aims to prepare students to better understand what is true and what is untrue in the world of the Internet, especially regards to in social media.